The Role of Islamic-Based Family Therapy in Reducing Domestic Conflicts: An Empirical Study in Sleman Regency - Tentrem Basuki; Khayatun Nufus Akhsnia (Islamic Counseling and Parenting Journal, 2026)
Domestic conflict remains a pervasive challenge in Indonesian Muslim families, yet empirically grounded interventions integrating Islamic values at the local level remain underexplored. The purpose of this study is to analyze the role of Islamic-based family therapy in reducing household conflict in Muslim families in Sleman Regency, by identifying the factors causing conflict, its impact on the quality of communication and emotional regulation, and the factors that determine the success of therapy. This study examines the role of Islamic-based family therapy in reducing domestic conflicts among Muslim households in Sleman Regency, Special Region of Yogyakarta. Employing a qualitative field research design, data were collected through in-depth interviews, observations, and documentation involving 12 informants comprising six married couples who had undergone a minimum of three Islamic-based family therapy sessions, three Islamic family counselors, and three religious extension workers, selected through purposive sampling. The findings reveal that Islamic-based family therapy contributes to conflict reduction through four principal mechanisms: (1) improvement of spousal communication quality grounded in Islamic communicative ethics; (2) strengthening of emotional self-regulation through the practice of sabr (patience) and muhasabah (self-reflection); (3) enhancement of spiritual awareness through structured worship activities; and (4) development of constructive problem-solving competencies through the principle of shura (deliberation). The study further demonstrates that sustained religious commitment and continuous counseling support are critical determinants of therapeutic success. These findings offer empirically grounded evidence that Islamic-based family therapy constitutes a holistic and culturally congruent intervention for enhancing family resilience in Muslim communities.